(untitled) (Archives of Criminology, 2018)
The present state of scientific knowledge suggests that individuals cannot be deprivedof fundamental human rights. Human dignity must be respected and protected,especially in the case of individuals in difficult circumstances. Prison is certainly notan easy place to be. People in custody can feel lonely, separated from their families,friends or working life. The difficult situation that they are facing can lead to loneliness,susceptibility to diseases, an increased risk of aggression and severance of family ties.People in such a situation can easily fall victim of assaults on human dignity. That iswhy the ruling elites should make every effort to ensure their rights.In those circumstances, prisoners’ rights must be guaranteed by law. In accordancewith the principle of proportionality enshrined in Article 31 section 3 of the Constitutionof the Republic of Poland, the rights and duties of persons remanded in custodyhave to be regulated by legislation, mainly by the Executive Penal Code. In addition,according to the rules laid down in Article 4 section 2 of the Executive Penal Code,imprisoned persons retain their civil rights, and any restrictions on their rights maybe justified only if they are stipulated by law and valid decisions based on statutorygrounds. However, it should not be overlooked that the final shape of the rights ofpersons remanded in custody is influenced by secondary legislation and even de cisionsof the director of a penitentiary unit or other officers. By way of example, prisoners’visiting rights have to be guaranteed by law. For example, if the relevant legislationensured that the prisoner has the right to visits by the family every month, such visitscould preferably take place at a convenient time, e.g. at weekends.The aim of this paper was to confront the legal acts with statutory and internationalregulations which impact on the situation of prisoners. This situation wascompared with the decisions of the European Court of Human Rights. Internalorders of penitentiary units laid down by their directors were analysed from twoperspectives. Firstly, the authors verified if the directors implemented their internalorders in pursuance of the law. The issue is that any limitation on the vested rights hasto be based on law. Secondly, it is important how selected human rights are respectedin the internal orders and whether any such limitations are justified in the light of the applicable law and ECHR jurisprudence. For example, such issues as waterand bath availability, the right to use electricity, walking conditions, right to visits byfamily and friends, telephone contacts and access to the Internet, practising faith wereexamined during the research. Penitentiary isolation impacts on the prisoners’ freedom,especially in some types of penitentiary units. Therefore, particular attention shouldbe paid to improve the detention conditions. However, it should not be forgotten thatthe deprivation of liberty is punishment in itself. There is no need to cause unnecessarysuffering, especially without legal grounds. By the same token, it is not necessary tomake the burden of isolation heavier. The authors pointed out solutions inserted intopenitentiary, accessing its relevance. Any restriction of the prisoners’ rights musthave a legitimate basis laid down by law. The financial standing of countries, prisonovercrowding and an insufficient number of officers cannot be an excuse for anygovernment. The penitentiary system should be organised in such a way as to ensurefull respect for the rights of all prisoners. T he paper also points to the lack of detailedregulations in individual units, despite the obligation for such regulations to exist. Aswell as other problems, there is also the issue of regulations which became too wideand general, contrary to the principle of legal certainty. In effect, it is difficult to enforcein practice some rights which are not expressly conferred by law.